Effect of Pure and Combine Hormone of Pregnant Mare Serum (PMSG) on Gonadosmatic Index, Hepatosomatic Index of Silver Pompano Fish (Trachinotus blochii) - Wiwin Kusuma Atmaja Putra; Tengku Said Razai (Airlangga University, 2017)
The research was title The Effect of Pregnant Mare Serum Gonadotropin (PMSG) Pure and Combinations against Gonadosomatik Index, Hepatosomatic Index Silver Pompano (Trachinotus blochii). The purpose of this research was to obtain the best hormone treatment to increase the gonadosomatic index and Hepatosomatic Index. This research used a Completely Randomized Design with 3 treatments and 3 replicates of fish. The treatments include Control (0.5 ml NaCl), PMSG (20 IU kg-1 fish body weight) and PG600 (20 IU. Kg-1 fish body weight). Parameters calculated include Gonadosomatic Index (GSI), Hepatosomatic Index (HSI) and Absolute Growth. The best results were PG600 treatment with Gonadosomatic Index (0.12±0.06), Hepatosomatic Index (2.29±0.15 %) and Absolute Growth (85±31.32 g) for 4 weeks. The conclusion of this study is the provision of pure PMSG and combination with a dose of 20 IU. Kg-1 body weight can increase gonadosomatik index, hepatosomatic index and absolute growth of Silver Pompano fish. Keywords : Silver Pompano Fish, PMSG, PG600, Gonadosomatic Index